2006
DOI: 10.1152/japplphysiol.00167.2006
|View full text |Cite
|
Sign up to set email alerts
|

Advancing age alters the expression of the ryanodine receptor 3 isoform in adult rat superior cervical ganglia

Abstract: Sympathetic nerves arising from the superior cervical ganglion (SCG) protect the cerebrovasculature during periods of acute hypertension and may play a role in homeostasis of target organs. The functions of these nerves depend on calcium release triggered by activation of ryanodine receptor (RyR) channels. The function of RyR channels is in part dependent on genetic expression and regulation by numerous protein modulators such as neuronal nitric oxide synthase (nNOS) neurons also found in the SCG. We have show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 65 publications
0
20
1
Order By: Relevance
“…In a report by Lu et al (42), RyR-1 mRNA was increased significantly in aged human cortical tissue from individuals that were not demented, which suggests that increased RyRs may have a protective or positive role to play in neuronal function. Furthermore, it has been shown recently that RyR-3 mRNA and protein levels are increased in the superior cervical ganglia of aged rats and may serve to protect neurons from oxidative stress by modulating and increasing the protein expression of neuronal nitric-oxide synthase (43). A clearer picture of how RyRs are involved in balancing normal and pathological aging is required before they can be considered a feasible therapeutic target.…”
Section: Discussionmentioning
confidence: 99%
“…In a report by Lu et al (42), RyR-1 mRNA was increased significantly in aged human cortical tissue from individuals that were not demented, which suggests that increased RyRs may have a protective or positive role to play in neuronal function. Furthermore, it has been shown recently that RyR-3 mRNA and protein levels are increased in the superior cervical ganglia of aged rats and may serve to protect neurons from oxidative stress by modulating and increasing the protein expression of neuronal nitric-oxide synthase (43). A clearer picture of how RyRs are involved in balancing normal and pathological aging is required before they can be considered a feasible therapeutic target.…”
Section: Discussionmentioning
confidence: 99%
“…However, as discussed above, protein levels are not the only important measure of RyR function, as activity of these channels is be regulated by several factors. Therefore, we extended our studies to investigate possible age-related changes in selected modulators of the RyR, including phosphorylation and nNOS levels which are known to modulate levels of cADPr (Vanterpool et al, 2006). We found that total phosphorylation of RyR channels was not altered with age, suggesting that steady state phosphorylation of RyR and hence regulation by this mechanism does not necessarily change with advancing age.…”
Section: Altered Expression Of Ryanodine Receptors (Ryr) and Modulatomentioning
confidence: 82%
“…Based on results of our most current studies and reviews (Vanterpool et al, 2005(Vanterpool et al, , 2006Buchholz et al, 2007; and our previous work and that of others we propose the following: With advancing age an alteration in [Ca 2+ ]i signaling and function of peripheral adrenergic neurons results from a complex interplay of mechanisms, including increased sensitivity of the NA release mechanism to calcium, decline in SERCA function that alters calcium buffering and refilling of SER calcium stores, reduced RyR3 and decline in nNOS levels, which in turn modulates cADPr levels. This combination ultimately reduces the capacity of the SER to release calcium and abolishes the CICR process.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations